Study on Transformer JED Cap Actuation Systems in the Field of Very Strong Electromagnetic Disturbances - Andrzej M. FARYŃSKI (Badania transformatorowych układów pobudzania spłonek JED w polu bardzo silnych zaburzeń elektromagnetycznych, 2020)
This work presents the results of research on the influence of strong external electromagnetic fields on the operation of JED spark caps activated by transformer systems. The tests were carried out in order to determine the conditions of safe use of JED caps installed in control systems of generators producing electric current pulses using the principle of an explosive magnetic field cumulation [1]. For this purpose, the measurements of the voltages induced in the transformer JED spark cap actuation system were performed using sinusoidal external current with an amplitude of 10 kA for a period of 15 microseconds. This current flowed at a distance from d = 10 mm to d = 40 mm from the axis of the ferrite cores of the applied transformers: a closed core with an outer diameter of 20 mm, an inner diameter of 10 mm and a height of 10 mm and an open core with a diameter of 6 mm and a length of 25 mm. The transformers used in Air Force Institute of Technology (AFIT, Poland) were placed alternately parallel and perpendicular to the axis of the current conductor. In the case of a transformer with a cylindrical open core perpendicular to the current axis, the induced voltages significantly exceeded the values at which the caps were activated (about 2 kV) and became lower than these values at d of about 40 mm. Toroidal closed cores provided induced voltages of up to 200 V (10 times lower) for all configurations tested. The measurements were performed using a system and methods developed at AFIT.
Keywords: Badania układów pobudzania spłonek